The Morphology of Seed-Bearing Plants in The Qur’an: A Thematic Analysis of Tantawi Jawhari and Tafsir Ilmi by the IndonesianMinistry of Religious Affairs - Andhiarizqi Mulyawan; Yudianto Achmad; Zakaria Husin Lubis; Ahmad Kamaluddin (Institut Pertanian Bogor, 2026)
The Qur'an's Natural Phenomena (Āyāt Kauniyyah) verses contain scientific clues, including one on seed-bearing plant morphology. The study aimed to explain Qur'anic references to seed-bearing plant morphology, as well as the interpretation of these verses in Tantawi Jauhari's Tafsir Al-Jawâhir fî Tafsîr Al-Qur'ân Al-Karîm and Lajnah Pentashihan Mushaf Al-Qur'an's Tafsir 'Ilmi Tumbuhan dalam Perspektif Al-Qur'an dan Sains. The qualitative approach used in this study was library research, with data gathered from a variety of relevant sources. The Qur'an is interpreted using the Al-Maudhu'i (thematic) methods. Both methods aimed to generate descriptive data by observing Qur'anic chapters and verses, as well as providing scientific insights into the subject. The Qur'an mentions seed-bearing plant morphology through physical descriptions and metaphors (amthāl) in 26 words throughout 39 chapters and 87 verses. The verses that provide complete interpretation of plant morphology in Tafsir Al-Jawâhir fî Tafsîr Al-Qur'ân Al-Karîm include Al An'am/6:99, which addresses floral morphology; An Naml/27:60, which examines roots, stems, and leaves; and Yasin/36: 80, which concentrates on the leaf. Meanwhile, in Tafsir 'Ilmi Tumbuhan dalam Perspektif Al-Qur'an dan Sains, Al An'am/6:99 is interpreted in terms of the